In the Case of Federalism v. Charter: The Processes and Outcomes of a Federalist Dialogue - Clarke, Jeremy (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
The Charter of Rights has long been criticized for the supposed failure of its processes and outcomes to comply with Canadian federalism. This paper challenges those suppositions. The examination of five Supreme Court cases [Ford (1988); Lavigne (1991); Advance Cutting (2001a); Dunmore (2001b); and Solski (2005a)] through the lens of a "federalist dialogue" reveals a process of Charter interpretation in which provinces, far from being excluded, actually play a central role. Furthermore, this dialogue has the potential to generate an outcome—Charter-federalism—that is consistent with Canada's moral foundations.